2021
DOI: 10.3892/etm.2021.10530
|View full text |Cite
|
Sign up to set email alerts
|

Primary, secondary or less frequent causes of immune thrombocytopenia: A case report

Abstract: Primary immune thrombocytopenia (ITP) is characterized by isolated low platelet count and it is a diagnosis of exclusion, contrasting to secondary ITP. Therefore, a positive diagnosis is difficult and requires extensive investigation. Some of the underlying conditions that are associated with ITP are lymphoproliferative disorders and infections, especially viral ones. In the present study, the case of a patient diagnosed with diffuse large B-cell lymphoma, who received chemotherapy and autologous hematopoietic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Secondary refers to thrombocytopenia caused by other diseases or drugs. Recent reports confirm that autoimmune diseases, patients with low cellular immune function, viral infections, and the use of drugs such as quinine and heparin are important causations of ITP [6–8] . Although RA and secondary ITP are common clinical diseases, we found that effective treatment of ITP is rarely reported in patients with RA in China.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Secondary refers to thrombocytopenia caused by other diseases or drugs. Recent reports confirm that autoimmune diseases, patients with low cellular immune function, viral infections, and the use of drugs such as quinine and heparin are important causations of ITP [6–8] . Although RA and secondary ITP are common clinical diseases, we found that effective treatment of ITP is rarely reported in patients with RA in China.…”
Section: Discussionmentioning
confidence: 54%
“…Recent reports confirm that autoimmune diseases, patients with low cellular immune function, viral infections, and the use of drugs such as quinine and heparin are important causations of ITP. [ 6 8 ] Although RA and secondary ITP are common clinical diseases, we found that effective treatment of ITP is rarely reported in patients with RA in China. Therefore, we reviewed the changes of drug therapy and laboratory tests in this patient, providing an important reference for the treatment of ITP with RA.…”
Section: Discussionmentioning
confidence: 98%
“…Primary ITP arises from several different mechanisms [15], such as the peripheral destruction of platelets opsonized by antiplatelet antibodies [16], impaired thrombopoiesis [17], and the T-cell-mediated destruction of platelets [18,19]; each pathogenic mechanism plays an independent role in generating thrombocytopenia (Figure 1). syndrome, rheumatoid arthritis, or an immunodeficiency state), a hematological condition (chronic lymphocytic leukemia, large granular lymphocytic leukemia, lymphoma, or autoimmune lymphoproliferative syndrome), or following therapy with drugs such as heparin and quinidine [5][6][7][8][9][10][11]. In children, it often occurs after a viral infection and is selflimiting in 80% of cases.…”
Section: Pathogenesismentioning
confidence: 99%
“…In adults, 80% of newly diagnosed patients have primary ITP, which is characterized by isolated thrombocytopenia. Secondary ITP is triggered or associated with another disease, such as a chronic infection (Helicobacter pylori, human immunodeficiency virus-HIV, hepatitis C virus-HCV, or cytomegalovirus-CMV), an autoimmune disease (lupus erythematosus, antiphospholipid syndrome, rheumatoid arthritis, or an immunodeficiency state), a hematological condition (chronic lymphocytic leukemia, large granular lymphocytic leukemia, lymphoma, 2 of 20 or autoimmune lymphoproliferative syndrome), or following therapy with drugs such as heparin and quinidine [5][6][7][8][9][10][11]. In children, it often occurs after a viral infection and is self-limiting in 80% of cases.…”
Section: Introductionmentioning
confidence: 99%